2014
DOI: 10.1179/1743284714y.0000000534
|View full text |Cite
|
Sign up to set email alerts
|

Friction stir welding of mild steel: Tool durability and steel microstructure

Abstract: In previous work, we have established a scheme that exploits a three-dimensional heat and mass flow model to assess tool durability and define the domains of satisfactory tool life in the context of welding difficult aluminium alloys. We now apply this scheme to the friction stir welding of steel, and extend the calculations to cover consequences on the microstructure of the steel while optimizing tool life. This is the first published model that covers both the processing parameters and the consequences on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 35 publications
5
18
0
Order By: Relevance
“…Therefore, long exposure time and high peak temperatures might be the cause of the largest coarsening in HZ. The simulated cooling rates at the stir zone were different from the advancing to the retreating sides, with differences around 4°C s −1 between opposing sites, similar to the model stated by De et al [29], who reported no significantly differences throughout the stir zone.…”
Section: Numerical Simulation Analysissupporting
confidence: 83%
See 1 more Smart Citation
“…Therefore, long exposure time and high peak temperatures might be the cause of the largest coarsening in HZ. The simulated cooling rates at the stir zone were different from the advancing to the retreating sides, with differences around 4°C s −1 between opposing sites, similar to the model stated by De et al [29], who reported no significantly differences throughout the stir zone.…”
Section: Numerical Simulation Analysissupporting
confidence: 83%
“…Due to plastic deformation during FSW, defects are generated, and energy is stored in the microstructure. This stored energy is much higher in a FSW than in a conventional hot rolling process [29], for example. In addition, the stored energy varies according to the analyzed position within the welded joint and might be related to the particles trajectory, as shown in Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Figure 4 shows the contours of the numerically computed cooling rates between 1073 and 773 K for various welding speeds and heat generation rates. The computed cooling rates are similar to those reported in the published literature for FSW of steels [7,12,26]. The cooling rate increases significantly with the increase in the welding speed and decreases gradually with the increase in the rate of heat input.…”
supporting
confidence: 80%
“…e l s e v i e r . c o m / l o c a t e / j m a d has been studied in detail by Kumar et al [14,15]. In the FSP of MMCs, the material undergoes intense plastic deformation resulting in the mixing of ceramic particles and the metal.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 98%